Health behavior and mental health by gender in Korean adults before, during, and after the COVID-19 pandemic - Jae Yeon Jeong; Yoo Mi Jeong (PLoS ONE, 2025)
Objective Coronavirus disease 2019 (COVID-19) has been a global health crisis, and its aftermath has had a profound impact on mental health and health behaviors of Korean adults. This study aimed to determine the health behavior and mental health among adults aged 19 years and older before, during, and after the COVID-19 pandemic. Methods We used 2019–2022 data from Korea National Health and Nutrition Examination Survey (KNHANES) to analyze a comparative assessment of drinking, smoking, sleep, and stress in 2019, 2020, 2021, and 2022. Chi-square, one-way ANOVA and logistic regression analysis was performed with using Stata version 18.5. Results The proportion of drinking more than four times a week was slightly lower in the early- and with-COVID-19 and higher in the pre- and post-COVID-19, and was the same in the analysis of gender. The proportion of smoking in men decreased over time, whereas that in women increased. Both gender increased weekday sleep time in the pre- and early-COVID-19, and decreased in the post-COVID-19. Stress was slightly reduced in the pre- and post-COVID-19 compared to early-COVID-19 in men, and has decreased in the post-COVID-19 in women. Comparing these variables adjusting for the sociodemographic variables by years, frequency of drinking decreased in 2020 and 2021 for both men and women, but there was no difference in 2022. There was no statistically significant difference in current smoking for both men and women. Suicidal ideation decreased in men in 2022, but increased in women during the early-COVID-19. Conclusions Drinking and smoking showed a somewhat positive pattern of behavior change, but in the post-COVID-19, unhealthy behaviors have increased again, requiring active health interventions.